2011
DOI: 10.1007/s10661-011-1924-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Enterococcus faecalis bacteria resistant to heavy metals and antibiotics in surface waters of the Mololoa River in Tepic, Nayarit, Mexico

Abstract: Heavy metal and antibiotic resistance have been shown to have a strong correlation in nature, and their inter-relation is an important subject of study. We report an analysis of surface waters of the Mololoa River in the municipality of Tepic, state of Nayarit, Mexico. This river has two distinctive sources of contamination: sewage waters and trash confinements. Our findings demonstrate a correlation between the river flow pattern and resistance to heavy metals or to heavy metals and antibiotics in isolated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
0
9
0
3
Order By: Relevance
“…The other two studies reported inconclusive evidence for an effect of the urban area on the prevalence of ARB in unidirectional systems (Fincher, Parker, & Chauret, ; Suzuki, Kajii, Nishiyama, & Iguchi, ). One study evaluated the impact of a sewage dump and found higher levels downstream compared to upstream (Goni‐Urriza et al., ), and one study evaluated a sewage site (Mondragón et al., ), reporting inconclusive evidence. One study that evaluated the impact of a leaky sewer on groundwater based on distance found no evidence for increase in ARB levels.…”
Section: Resultsmentioning
confidence: 99%
“…The other two studies reported inconclusive evidence for an effect of the urban area on the prevalence of ARB in unidirectional systems (Fincher, Parker, & Chauret, ; Suzuki, Kajii, Nishiyama, & Iguchi, ). One study evaluated the impact of a sewage dump and found higher levels downstream compared to upstream (Goni‐Urriza et al., ), and one study evaluated a sewage site (Mondragón et al., ), reporting inconclusive evidence. One study that evaluated the impact of a leaky sewer on groundwater based on distance found no evidence for increase in ARB levels.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular description of bacterial communities of aquatic systems linked to affected sites from mining or industrial activities has brought very valuable information for the identification of biomonitoring organisms (Harwood et al , 2009;Mondragón et al, 2011;Paul et al, 2013). At present, the genetic characterization and the metabolic routes of bacterial species with the ability to reduce or oxidize some metals and other pollutants, is one of the main goals in the biotechnological research in Mexico.…”
Section: Monitoring Of Pollution and Pathogensmentioning
confidence: 99%
“…La descripción molecular de comunidades bacterianas de sistemas acuáticos asociados a sitios impactados por actividades mineras o industriales ha proporcionado información muy valiosa para la identificación de organismos biomonitores (Harwood et al, 2009;Mondragón et al, 2011;Paul et al, 2013). La caracterización genética y de las rutas metabólicas de especies bacterianas capaces de reducir u oxidar ciertos metales y otros contaminantes es uno de los objetivos primordiales de la investigación biotecnológica en México.…”
Section: Monitoreo De Contaminación Y Patógenosunclassified
“…Heavy metals can lead to degradation of marine ecosystems by decreasing species variety over accretion of metals in living animals and food chains [2]. Moreover, human activities also contributed to the deposition of heavy metals in the environment the condition is worsened by accumulation through food sources and finally lead to serious health and ecological problems [3]. Heavy metals can be discharged into the marine environment through many ways such as industries, wastewaters, and domestic effluents [4].…”
Section: Introductionmentioning
confidence: 99%